2007
DOI: 10.1111/j.1460-9568.2007.05581.x
|View full text |Cite
|
Sign up to set email alerts
|

Challenging the omnipotence of the suprachiasmatic timekeeper: are circadian oscillators present throughout the mammalian brain?

Abstract: The suprachiasmatic nucleus of the hypothalamus (SCN) is the master circadian pacemaker or clock in the mammalian brain. Canonical theory holds that the output from this single, dominant clock is responsible for driving most daily rhythms in physiology and behaviour. However, important recent findings challenge this uniclock model and reveal clock-like activities in many neural and non-neural tissues. Thus, in addition to the SCN, a number of areas of the mammalian brain including the olfactory bulb, amygdala,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
267
1
7

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 312 publications
(283 citation statements)
references
References 297 publications
(360 reference statements)
8
267
1
7
Order By: Relevance
“…Differences of expression may originate in a differential role for both proteins as respective mutants show altered patterns of Cry1 expression in ad libitum and HF conditions. It reinforces the growing hypothesis that there is not one single clock, but a system of multiple brain oscillators (Roenneberg and Merrow, 2003;Guilding and Piggins, 2007) ticking with different clock hands and differentially sensitive to nutritional cues. It would be interesting to distinguish between motivational and metabolic responses to hypocaloric feeding and their interpretation in each forebrain region.…”
Section: Circadian Oscillations In the Forebrain Of Mice Fed With A Hsupporting
confidence: 79%
See 2 more Smart Citations
“…Differences of expression may originate in a differential role for both proteins as respective mutants show altered patterns of Cry1 expression in ad libitum and HF conditions. It reinforces the growing hypothesis that there is not one single clock, but a system of multiple brain oscillators (Roenneberg and Merrow, 2003;Guilding and Piggins, 2007) ticking with different clock hands and differentially sensitive to nutritional cues. It would be interesting to distinguish between motivational and metabolic responses to hypocaloric feeding and their interpretation in each forebrain region.…”
Section: Circadian Oscillations In the Forebrain Of Mice Fed With A Hsupporting
confidence: 79%
“…A number of extra-SCN oscillators have been identified in the mammalian forebrain (reviewed in Guilding and Piggins, 2007). Here we found that PER1 immunoreactivity (IR) is observed alone in the DMH, aPirC and dST and concomitant with PER2 in the PVT, CA1, DG, CEA and Arc.…”
Section: Circadian Oscillations In the Forebrain Of Mice Fed Ad Libitummentioning
confidence: 66%
See 1 more Smart Citation
“…Abnormal rhythms of melatonin secretion has been associated with childhood and adult ADHD. 9,10 Cortisol circadian profiles have been reported to be either unaltered in ADHD 12 or altered in association primarily with the hyperactive subtype of ADHD. 13,14 The molecular basis of such circadian rhythm generation consists of positive and negative transcriptional/translational feedback loops of 'clock' genes and their protein products, and single-nucleotide polymorphism in clock genes have been associated with ADHD.…”
Section: Introductionmentioning
confidence: 99%
“…11 The master clock is in the suprachiasmatic nuclei (SCN) of the hypothalamus and it is entrained to the 24 h day via retinal photic input with further semiautonomous oscillators present throughout the brain and periphery. 12 SCN output is responsible for driving circadian rhythms in a number of hormones, including melatonin and cortisol. Abnormal rhythms of melatonin secretion has been associated with childhood and adult ADHD.…”
Section: Introductionmentioning
confidence: 99%